Application of High Electric Field Strength Microwave Energy for Processing Ores and Minerals - S. Kingman; D. Whittles; N. Miles; S. Bradshaw (International Mineral Processing Congress, 2003)
The influence of microwave energy at high electric field strength on ore strength has been investigated. Two ores of varying mineralogy were treated in both multimode and single mode microwave cavities. After treatment, any change in strength relative to untreated ore was established. It was shown that in the multimode cavity reduction in strength was related to the applied power level. Results of tests carried out in the single mode cavities showed that, for both ores, reductions in ore strength > 50% could be achieved in very short periods (<1 second). Thermal stress analysis showed that the mechanism of microwave induced failure was the development of tangential stresses at the grain boundaries. It was concluded that operation at 915 MHz with high power and short residence times gives feasible scale-up possibilities.